Capsaicin enhances erlotinib-induced cytotoxicity via AKT inactivation and excision repair cross-complementary 1 (ERCC1) down-regulation in human lung cancer cells. Issue 3 (26th March 2019) - Chen, Jyh-Cheng; Ko, Jen-Chung; Yen, Ting-Chuan; Chen, Tzu-Ying; Lin, Yuan-Cheng; Ma, Peng-Fang; Lin, Yun-Wei
Graphical Abstract: Abstract: Capsaicin, a natural active ingredient of green and red peppers, has been demonstrated to exhibit anti-cancer properties in several malignant cell lines. Excision repair cross-complementary 1 (ERCC1) has a leading role in the nucleotide excision repair (NER) process because of its involvement in the excision of DNA adducts. Erlotinib (Tarceva R ) is a selective epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor that has demonstrated clinical activity in non-small cell lung cancer (NSCLC) cells. However, whether capsaicin and erlotinib could induce synergistic cytotoxicity in NSCLC cells through modulating ERCC1 expression is unknown. In this study, capsaicin decreased the ERCC1 expression in an AKT inactivation dependent manner in two human lung adenocarcinoma cells, namely, A549 and H1975. Enhancement of AKT activity by transfection with constitutive active AKT vectors increased the ERCC1 protein level as well as the cell survival by capsaicin. Moreover, capsaicin synergistically enhanced the cytotoxicity and cell growth inhibition of erlotinib in NSCLC cells, which were associated with the down-regulation of ERCC1 expression and inactivation of AKT in A549 and H1975 cells. Together, these results may provide a rationale to combine capsaicin with erlotinib for lung cancer treatment.